O método investigativo em aulas teóricas de química: estudo das condições da formação do espírito científico - Kasseboehmer, Ana Cláudia (2011)
This work aims to understand the conditions that can lead to the formation of the scientific spirit applying investigative problems in theoretical classes of chemistry. The main theoretical reference that guided this research was Bachelard. Two types of investigative activities were prepared: the first one was related to the understanding of phenomena, in which case the students were asked to elaborate an explanation for the occurrence of that phenomenon, using scientific concepts and strategies to verify whether their hypothesis was consistent. The other type of investigation refers to the study of chemical processes developed by the human being and the students were asked to offer suggestions for procedure to solve the problem. In both cases few clues were given so that they could use. At the beginning of the year, a power point presentation was done to the students to defend the idea of the pleasure that studying can proportionate and an exercise was done to practice de elaboration of hypothesis and strategies of verification. After the teacher explain de concepts required to each investigation, an investigative activity was proposed to the students. At the follow week, after taking the answers back from the students, a group discussion was made in which the students were encouraged to expose their assumptions, strategies to check and criticize the ideas of colleagues. After each group discussion, students were interviewed. Teachers were interviewed at the beginning of the project, the end of first semester and the end of data collection. Students completed questionnaires at the beginning of the collection, during and at the end of the project. The research demonstrated that the application of theoretical problems in chemistry classes demonstrated ability to teach about the nature of science, as well as a very positive acceptance by students. Thus, it was observed that the investigative activities impacted in different ways in public and in private schools. The students in private schools used the concepts they learned to develop their hypotheses, showing greater academic efficiency. On the other hand, they showed less satisfaction and less freedom to innovate in their proposals. The public school students, in turn, felt more satisfaction in dealing with the project and showed greater freedom to create ideas, which has been hampered by observed conceptual problems. The data and results of this research allow suggesting that three factors contribute to the formation of the scientific spirit: knowledge about the nature of science; the domain of scientific concepts and a willingness to immerse themselves in scientific problems.